2023
DOI: 10.1002/hast.1477
|View full text |Cite
|
Sign up to set email alerts
|

Wrestling with Social and Behavioral Genomics: Risks, Potential Benefits, and Ethical Responsibility

Abstract: Social and behavioral scientists are increasingly frequently collaborating with geneticists or adapting the methods of genetics research to investigate how genomic differences are associated with differences in a wide variety of behavioral and social phenotypes. The huge and varied range of phenotypes investigated in social and behavioral genomics (SBG) research, broadly construed, includes smoking and eating behavior, schizophrenia, attention deficit-hyperactivity disorder (ADHD), a sense of well-being, intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 114 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…Recent studies that use polygenic risk scores (summing the influence of all identified relevant genes) show that genetic variation accounts for at most 12-16% of the variance in educational attainment (years of education measured in a sample of some 3 million participants; Okbay et al, 2022). Moreover, their effects are not direct and include effects of geneenvironment correlation and assortative mating (Meyer et al, 2023 for a review).…”
Section: Should the Causes Of A Disorder Be A Part Of Its Definition?mentioning
confidence: 99%
“…Recent studies that use polygenic risk scores (summing the influence of all identified relevant genes) show that genetic variation accounts for at most 12-16% of the variance in educational attainment (years of education measured in a sample of some 3 million participants; Okbay et al, 2022). Moreover, their effects are not direct and include effects of geneenvironment correlation and assortative mating (Meyer et al, 2023 for a review).…”
Section: Should the Causes Of A Disorder Be A Part Of Its Definition?mentioning
confidence: 99%
“…GWAS and PGS SNP associations may be spurious or non-causal, as, like the earlier candidate gene studies, they are subject to potential environmental confounds and other problems. GWAS/PGS problems and potential biases include population stratification, a lack of individual predictive value, the practice of increasing the sample size to find statistically significant gene associations, that "variation explained by" does not mean "caused by," and the potential fishing expedition aspect of "hypothesis-free" studies in which researchers base their conclusions on statistically significant yet chance associations (see Baverstock, 2019;Burt, 2023;Charney, 2022;Coop & Przeworski, 2022;Gusev, 2023;Joseph & Boyle, 2024;Meyer et al, 2023;Non & Cerdeña, 2023;Richardson & Jones, 2019;Turkheimer, 2016Turkheimer, , 2019Veller & Coop, 2024).…”
Section: No Gene Discoveries Were Cited In the Bell Curvementioning
confidence: 99%
“…The concept of ‘dysgenic fertility’ stems from eugenic ideology, which was popularized in the ninteenth century by Charles Darwin's cousin Francis Galton [ 1 , 2 ]. Galton and other eugenicists believed that human populations can be ‘improved’ through selective reproduction; encouraging those with ‘desirable’ traits to have children while discouraging reproduction in those with ‘undesirable’ traits.…”
Section: What Is ‘Dysgenic Fertility’?mentioning
confidence: 99%